Developmental Epidemiology of Pediatric Anxiety Disorders - Warner, Emily N; Ammerman, Robert T; Glauser, Tracy A; Pestian, John P; Agasthya, Greeshma; Strawn, Jeffrey R (Child and adolescent psychiatric clinics of North America, 2023)
This review summarizes the developmental epidemiology of childhood and adolescent anxiety disorders. It discusses the coronavirus disease of 2019 (COVID-19) pandemic, sex differences, longitudinal course, and stability of anxiety disorders in addition to recurrence and remission. The trajectory of anxiety disorders-whether homotypic (ie, the same anxiety disorder persists over time) or heterotypic (ie, an anxiety disorder shifts to a different diagnosis over time) is discussed with regard to social, generalized, and separation anxiety disorders as well as specific phobia, and panic disorder. Finally, strategies for early recognition, prevention, and treatment of disorders are discussed.